The Impact of Ethical Leadership on Employee Performance: The Mediating Role of Employee Engagement, Organizational Citizenship Behavior (OCB), and Interprofessional Team Collaboration As Moderating Variables In The Upt Samsat North Aceh Office - Baluntara, Satria; Musnadi, Said; Kesuma, T.Meldi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the impact of ethical leadership on employee performance: the mediating role of employee engagement, organizational citizenship behavior, and interprofessional team collaboration as moderating variables in the upt samsat north aceh office. Adopting a quantitative approach, survey data were collected from a diverse sample of employees across various industries. Statistical techniques, including regression and correlation analyses, were employed to examine the relationships among the variables. The results indicate that employee engagement, ethical leadership, cross-professional collaboration, and OCB all have a significant positive effect on employee performance. Specifically, higher levels of engagement, ethical leadership, and collaborative practices are strongly associated with improved performance outcomes. Furthermore, OCB emerged as a critical predictor of enhanced employee performance. These findings underscore the importance of cultivating a positive organizational climate that emphasizes employee engagement, ethical leadership, interprofessional collaboration, and a culture that encourages discretionary effort. The study offers valuable managerial insights for improving performance through targeted strategies that strengthen these key organizational dimensions.